2019
DOI: 10.1080/21691401.2019.1699825
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Silencing hsa_circ_PVT1 (circPVT1) suppresses the growth and metastasis of glioblastoma multiforme cells by up-regulation of miR-199a-5p

Abstract: 2020) Silencing hsa_circ_PVT1 (circPVT1) suppresses the growth and metastasis of glioblastoma multiforme cells by up-regulation of miR-ABSTRACT Background: Glioblastoma multiforme (GBM) is one of the most prevailing primary brain tumours among adults and most aggressive cancers. Despite multiple developments in medical and surgical treatments, GBM is still a deadly disease with a high mortality rate. Here, this study was performed to investigate the function of circPVT1 on GBM. Methods: CCK-8 and flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Meanwhile, EMT inhibited apoptosis and regulated the expression of transcription factors, such as Snail, Slug, ZEB1/2 and TWIST1/2 [17]. Studies have shown that cytokines in the microenvironment of ovarian cancer, including ET-1, TGF-β and EGF, can mediate the occurrence of EMT and activate regulate relevant signaling pathways to promote the progression of ovarian tumor [18][19][20]. However, whether HAL interacts with EMT pathway in serous ovarian cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, EMT inhibited apoptosis and regulated the expression of transcription factors, such as Snail, Slug, ZEB1/2 and TWIST1/2 [17]. Studies have shown that cytokines in the microenvironment of ovarian cancer, including ET-1, TGF-β and EGF, can mediate the occurrence of EMT and activate regulate relevant signaling pathways to promote the progression of ovarian tumor [18][19][20]. However, whether HAL interacts with EMT pathway in serous ovarian cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the research performed by Wang et al, it was illustrated that microRNA-199a-5p repressed glioma progression, invasion, and migration in vitro by directly targeting magnesium transporter 1 (MAGT1) [98], whereas according to Zhang et al the same effect was obtained by targeting the membrane-associated ring-CH-type finger 8 (MARCH8) [99]. In glioblastomas, the upregulation of miR-199a-5p by circPVT1 silencing hindered viability, and migration, while also positively influencing apoptosis [100]. Considering the divergent functions of miR-199a-5p concerning brain tumors, it is possible that multiple pathways with opposing effects are also involved in BAVMs.…”
Section: Mir-199a-5pmentioning
confidence: 99%
“…As a hot topic of non-coding RNA research in recent years, circRNAs have been found to play important functions in numerous life activities (Anczukow et al, 2015;He et al, 2016;Wang et al, 2021). The current modes of action of circRNAs include ceRNA regulation, encoding small peptides, and binding proteins to exert functions (Li et al, 2018;Wang et al, 2019;Chi et al, 2020). Although the latter two modes of action are currently uncommon, a growing number of studies suggest that circRNAs function in a variety of ways.…”
Section: Discussionmentioning
confidence: 99%